Diversidade e prática docente quilombola: interlocuções entre o ensino de química e a educação intercultural - FELIX, Joseane Ferreira Costa (2024)
Education from a perspective of cultural diversity has been present in the teaching process for some time. Known at first as popular education, it gained strength and came to be understood as education for intercultural relations. Thus, this dissertation deals with the teaching of Chemistry from a perspective of cultural diversity, with the aim of analyzing the pedagogical posture of teachers from the perspective of intercultural education, applied to the teaching of Chemistry in state public high schools located in quilombo communities in Maranhão. The aim was to contribute to teaching that takes into account ethnic-racial relations and education with a view to cultural diversity in Maranhão quilombola schools. To this end, the study adopted, in its theoretical support, the vision of the following authors: Candau (2008, 2011, 2016, 2020), Fleuri (2000, 2002a, 2002b, 2003), Gomes (2003, 2005), McLaren (2000), Santiago, Akkari and Marques (2013), among others who have also contributed to the field of diversity in Chemistry teaching. The research used exploratory research with a qualitative approach, whose participants were teachers who teach Chemistry in quilombola schools in Maranhão. For data collection, the following instruments were used: questionnaire, to find out the profile of the participating teachers, and semi-structured interview. Content Analysis (Bardin, 2016) was used to interpret and analyze the data, categorizing the units of meaning and structuring them into a systemic network. As a result, we were able to understand that diversity is broad and encompasses many themes. Thus, working on diversity means bringing diverse content into schools, building dialogues on cultural and religious issues and, above all, discussing racial prejudice. It is recognizing the history of a people, knowing how to understand and respect others, living with differences in a respectful environment and understanding that we are equal in rights and duties, but in a different world. To this end, it is necessary to understand that the different/heterogeneous should not be equated/homogenized and to conceive that teaching, learning, reflecting, and debating about identities is a fundamental exercise, made possible by education from an intercultural perspective. It was also found that intercultural education breaks down the barriers of prejudice and stereotypes and, above all, dispels the idea of homogenizing teaching, as it seeks to consider the student’s daily life, culture, and origin.